Balanced scorecard - surpassed method? (a study focused on dynamic balanced scorecard) - Kožená, Marcela; Chládek, Tomáš (Univerzita Pardubice, 2010)
Balanced Scorecard method is with no doubt a modern tool for evaluating and measuring of competitiveness of a company. Aim of this study is to answer a question, whether has BSC method been surpassed? As a source of relevant data were used scientific studies similar to this one which were elaborated in Japan, China and the USA. These studies refer to simple fact - original concept of BSC needs to undertake a dynamization process to keep up with turbulent environment of our world. Other goals of this study are analysis and evaluation of disadvantages of BSC method, possible effect of above mentioned dynamization for individual companies or comparison of implementation processes of BSC and DBSC.
Keywords: balanced scorecard; dynamic balanced scorecard; competitiveness; competitive advantage measurement